Impact of Good Governance on Development in Kenya, the Case of Garissa County - Mohamed Ali Ismail; Ahmed Osman Warfa (Budapest International Research and Critics University, 2023)
Good governance is regarded as significant when it’s making progress towards achieving objective. Good governance cannot be underrated since it plays a vital role for a healthy, independent, robust economy and culture. Economy consists of three types that include economic, political and administrative. The government of the day is sole responsible in nurturing these types of economy. Economy is a backbone for any developing country and contributes a lot to the development of country’s infrastructure, for this purpose the government should promote accountability of resource through proper allocation and eliminating corruption. Therefore the strength of good governance depends on economic welfare, reduced corruption, resisting political instability and unrest and enhancing basic need for the nation through effective administration. The aim of this article is to examine the concept of good governance and the impact on economic development in Kenya. The population of the study constituted of staff employed by national and county government. Both primary and secondary data was employed in the study. The study has found that though good governance indicators had reflected in parts of the government sectors, still some potential pillars are missing hence compromising development. Moreover, in order to strengthen good governance both tiers of government should nurture element good governance in order to stimulate economic growth since good governance is backbone to economic development.